Implementation of Educational Programmes and Policies: The Study of Education Funding, Universal Basic Education (UBE) and Teacher Education - Osarenren-Osaghae, R. I.; Adesuwa Evelyn, Ogieva; Abieyuwa, Osabuohien – Osarumwense; Kennedy, Oribhabor (Progress in Language, Literature and Education Research Vol. 8, 2024)
Education has been an excellent tool to indeed bring about advancement and development in the nation as proven by advanced nations of the world. The problem of this study is that Nigeria seems not to be growing educationally but rather diminishing and this has affected every facet of life in Nigeria. The present state of the Nigeria education system brings worry to the hearts of all stakeholders because education goals such as producing skilled and professionally competent graduates, basic education for all, education for technological advancement, all to fulfil the dream of national development and prosperity, are yet farfetched from being a reality. Literatures were reviewed on three of the policies in education, which include: education funding, universal basic education and teachers’ education for better understanding. In Nigeria, teacher education through colleges of education both at the federal and state government levels was meant to improve teacher preparation. Teachers are supposed to be the most intelligent, best breeds for obvious reasons as they are the ones trained to train others. The review discussed and highlighted the problems, potholes and patches of these policies as examples of the reason why education development in Nigeria is yet at the bottom of the success ladder. Conclusions were reached and recommendations were proffered.